Design, Synthesis, and Characterization of N-Oxide-Containing Heterocycles with in Vivo Sterilizing Antitubercular Activity - Dos Santos Fernandes, Guilherme Felipe [UNESP]; De Souza, Paula Carolina [UNESP]; Moreno-Viguri, Elsa; Santivañez-Veliz, Mery; Paucar, Rocio; Pérez-Silanes, Silvia; Chegaev, Konstantin; Guglielmo, Stefano; Lazzarato, Loretta; Fruttero, Roberta; Man Chin, Chung [UNESP]; Da Silva, Patricia Bento [UNESP]; et al. (American Chemical Society (ACS), 2017)
Tuberculosis, caused by Mycobacterium tuberculosis (Mtb), is the infectious disease responsible for the highest number of deaths worldwide. Herein, 22 new N-oxide-containing compounds were synthesized followed by in vitro and in vivo evaluation of their antitubercular potential against Mtb. Compound 8 was found to be the most promising compound, with MIC90 values of 1.10 and 6.62 μM against active and nonreplicating Mtb, respectively. Additionally, we carried out in vivo experiments to confirm the safety and efficacy of compound 8; the compound was found to be orally bioavailable and highly effective, leading to a reduction of Mtb to undetectable levels in a mouse model of infection. Microarray-based initial studies on the mechanism of action suggest that compound 8 blocks translation. Altogether, these results indicate that benzofuroxan derivative 8 is a promising lead compound for the development of a novel chemical class of antitubercular drugs.